Talking about tags: An exploratory study of librarians’ perception and use of social tagging in a public library - Clements, Lucy; Liew, Chern Li (Electronic library, 2016)
Focuses on how librarians perceive and use user-assigned subject heading tags, as compared to formal subject heading tags. Source: National Library of New Zealand Te Puna Matauranga o Aotearoa, licensed by the Department of Internal Affairs for re-use under the Creative Commons Attribution 3.0 New Zealand Licence.